2018
DOI: 10.1182/blood-2018-99-115959
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Lymphocytic Leukemia Patients with IGH Rearrangements Are Characterized By a Distinct Genetic Landscape with Prognostic Implications

Abstract: Background: Chromosome 14q32 rearrangements involving the immunoglobulin heavy chain gene (IGH) affect less than 5% of chronic lymphocytic leukemia (CLL) patients. Their clinical course is aggressive and the outcome, worse than other CLL subtypes (Cavazzini et al, 2008; Gerrie et al, 2012). However, the biology of CLL showing IGH rearrangements (CLL-IGHR) is not completely defined. The identification of novel recurrent mutations in CLL by next generation-sequencing (NGS) has offered a more comprehensive view i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…This alteration occurred simultaneously with other cytogenetic alterations in 76% of cases, being the most frequent in the del(13q) and trisomy 12. This enrichment of trisomy12 has been previously reported, not only in CLL with del(14q), 4,5,17,35 but also in other neoplasms with this aberration, 6 and furthermore, with other IGH abnormalities such as IGH translocations, 13,16,36–39 suggesting a strong cooperation between both genetic events.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This alteration occurred simultaneously with other cytogenetic alterations in 76% of cases, being the most frequent in the del(13q) and trisomy 12. This enrichment of trisomy12 has been previously reported, not only in CLL with del(14q), 4,5,17,35 but also in other neoplasms with this aberration, 6 and furthermore, with other IGH abnormalities such as IGH translocations, 13,16,36–39 suggesting a strong cooperation between both genetic events.…”
Section: Discussionsupporting
confidence: 82%
“…It is noteworthy that the 14q32.33 chromosomal band, which contains IGH locus, is clinically relevant in CLL, since the mutational status of its variable chain (IGHV) represents one of the most powerful prognostic markers 7,8 . Moreover, 14q32 rearrangements involving IGH gene have also a prognostic impact in CLL, showing these patients an intermediate‐adverse outcome and a distinct mutational profile from other classic cytogenetic subgroups 9–14 . Furthermore, the long arm of chromosome 14 has been shown to be involved not only in reciprocal rearrangements in CLL, but also in deletions 4,5,15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the simple deletion of 17p, the unbalanced translocation resulted in the loss of 17p, such as dic(17;18)(p11.2;p11.2), 10 which may correlate with a poorer outcome. Regarding the abnormality in 14q32 in the present case, a recent study indicated that chromosome 14q32 rearrangements/translocations involving the immunoglobulin heavy chain ( IGH ) were associated with an intermediate‐adverse outcome 11 . The co‐existence of lymphoproliferative neoplasms and myeloproliferative neoplasms is suggested to be a rare event.…”
Section: Discussionmentioning
confidence: 61%
“…Regarding the abnormality in 14q32 in the present case, a recent study indicated that chromosome 14q32 rearrangements/ translocations involving the immunoglobulin heavy chain (IGH) were associated with an intermediate-adverse outcome. 11 The co-existence of lymphoproliferative neoplasms and myeloproliferative neoplasms is suggested to be a rare event. Under this condition, the lymphoproliferative disorder presents a clinically indolent course with a low-risk biological profile.…”
Section: Discussionmentioning
confidence: 99%